Macroeconomic dynamics and reallocation in an epidemic: Evaluating the "Swedish solution" - Dirk Krueger; Harald Uhlig; Taojun Xie (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
In this paper, we argue that endogenous shifts in private consumption behavior across sectors of the economy can act as a potent mitigation mechanism during an epidemic or when the economy is re-opened after a temporary lockdown. We introduce a SIR epidemiological model into a neoclassical production economy in which goods are distinguished by the degree to which they can be consumed at home rather than in a social, possibly contagious context. We demonstrate within the model, that the "Swedish solution" of letting the epidemic play out without much government intervention and allowing agents to reduce their overall consumption as well as shift their consumption behavior towards relatively safe sectors can lead to substantial mitigation of the economic and human costs of the COVID-19 crisis. We argue that significant seasonal variation in the infection risk is needed to account for the two-wave nature of the pandemic. We estimate the model on Swedish health data and show that it predicts the dynamics of weekly deaths, aggregate as well as sectoral consumption, that accord well with the empirical record and the two-waves for Sweden for 2020 and early 2021. We also characterize the allocation a social planner would choose and how it would dictate sectoral consumption patterns. In so doing, we demonstrate that the laissez-faire outcome with sectoral reallocation mitigates the economic and health crisis but possibly at the expense of unnecessary deaths and too massive a decline in economic activity.
Keywords: E52; E30; 330; Epidemic; Coronavirus; Macroeconomics; Sectoral Substitution